Pracodawca jako kategoria systemu prawa - Kuczyński, Tadeusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The subject matter of this study is an analysis of the diversity of meanings and normative contexts assigned to the concept of employer in the legal system. The role of the general, and at the same time model, legal act creating the systemic concept of employer is fulfi lled by the Labour Code. The technique of determining the meaning of this concept, used in the provisions of law, takes the form of regulations referring to the Labour Code or norms establishing their own statutory meaning of the term. There are also provisions that formulate inadequate defi nitions, which results in a classifi - cation of the concept of employer into a wrong category. A review of the relevant provisions of law indicates that the said regulations do not, in many situations, satisfy the principle of terminological consistency or the requirement of systemic coherence. This applies to norms in which, instead of the systemic category of employer, descriptive expressions are used that only indirectly indicate that the relationship regulated concerns the employment binding the employer and the employee, to regulations that introduce only an apparent, and not a real, statutory modifi cation of the code concept under consideration, and, fi nally, to norms that, due to their faulty treatment of linguistic issues relating to the rational creation of law, do not meet the requirement of the said adequacy.
Keywords: employer; legal system; concept of employer